Coping with racism : exploring the experiences of the post-1994 generation of black students at a historically whites-only university in South Africa - Sibanda, Sharon (University of Pretoria, 2021)
Mini Dissertation (MA (Counselling Pyschology))--University of Pretoria, 2021.